1995
DOI: 10.1080/00288233.1995.9513149
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of white clover cultivars under intensive grazing, as affected by high nitrogen fertiliser application

Abstract: Nine cultivars of white clover (Trifolium repens L.) were grown with perennial ryegrass (Lolium perenne L.) and their productivity was determined over 3 years under nitrogen (N) fertiliser regimes of 0 or 390 kg N/ha per year. The site was grazed by sheep at 3-or 6-week intervals and after each grazing N fertiliser was applied at 0 or 30 kg N/ha. Fertiliser N application increased total annual pasture production by 25-31%, with the largest proportional responses occurring in autumn and winter. White clover pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
(20 reference statements)
2
10
1
Order By: Relevance
“…Although the differences between the experiments in terms of clover yield cannot be analysed statistically they are low in comparison with other published work (e.g. Ledgard et al 1995).…”
Section: Methodscontrasting
confidence: 57%
See 1 more Smart Citation
“…Although the differences between the experiments in terms of clover yield cannot be analysed statistically they are low in comparison with other published work (e.g. Ledgard et al 1995).…”
Section: Methodscontrasting
confidence: 57%
“…1 2 3 4 5 6 7 8 9 10 Years Previous reports have found a strong and durable negative correlation between white clover and grass DM yields (e.g. Ledgard et al 1995). In the present study this was found only to a limited extent, predominantly in harvest years 5-8.…”
Section: Methodssupporting
confidence: 42%
“…Greater rates of spring growth and response to N fertilizer application favor the competitive ability of grass Body condition score was on a scale of 1 to 5 (1 = emaciated and 5 = extremely fat, using 0.25 increments). *P < 0.05; ***P < 0.001. over clover within GWc swards (Frame and Newbould, 1986;Ledgard et al, 1995;Andrews et al, 2007). Frequent harvesting of the additional grass growth resulting from the fertilizer N minimizes shading and, to some extent, suppresses grass growth to the benefit of clover (Harris and Clark, 1996;Ledgard et al, 2001).…”
Section: Sward Measurementsmentioning
confidence: 99%
“…Seasonal climatic conditions and pasture production data for three years after establishment were presented by Ledgard et al (1996). Seasonal climatic conditions and pasture production data for three years after establishment were presented by Ledgard et al (1996).…”
Section: Fig 3 Relationship Between White Clover Production and N2mentioning
confidence: 99%